Functional electrical stimulation in upper extremity recovery of hemiparetic patients after stroke - Soares, Antonio Vinicius; Poluceno, Leila; Cremonini, Caroline da Rosa; Ponsoni, Priscila Baracho; Domenech, Susana Cristina; Borges Júnior, Noé Gomes (Acta Fisiátrica, 2012)
The rehabilitation of the upper limb of hemiparetic patients by stroke is a major challenge. Among the various therapeutic resources used, functional electrical stimulation (FES) has been a popular avenue explored in treatment programs for these patients. Objective: To evaluate the effects of FES on wrist and finger extensors in a specific task (ST). Methods: We conducted a pre-experimental study (pre and post-tests) with eight chronic patients with a mean age of 63.4 years (± 6.1). The evaluation parameters were for manual mobility by the hand movement scale (EMM), grip strength by dynamometry (Din), dexterity of the upper limb by the box and blocks test (CB) and the 9-pin and holes test (9PB), spasticity by the modified Ashworth scale (MAS), and functional independence by the Barthel index (BI). The ST chosen was performing the movement of reaching and grasping plastic bottles of different sizes with the affected upper limb in different combinations of positions for a total maximum of 54 repetitions per session. FES was used to assist the hand in grabbing and holding the object during the ST. There was a mean of 20 sessions with attendance twice a week. Results: The results showed improvement in all parameters, the difference was statistically significant in all the tests, except for Din. Conclusion: In this sample, FES in the proposed ST resulted in improved performance in the upper limb function of patients undergoing treatment.